INTERNET TECHNOLOGIES AS A FACTOR OF INCREASING THE COMPETITIVENESS AND COMPETITIVE STABILITY OF SERVICE ORGANIZATIONS - A. K. Kiryukhin; D. V. Akopyan; I. A. Suvorov (Вестник университета)
Presently, the use of Internet technologies is an absolute advantage on the way to the successful functioning of an enterprise in any sphere of economy. The increasing unpredictability of the external environment, the variability of consumer preferences are increasingly transforming competition in the markets of goods and services, from the industrial to the information plane. Under such conditions, the role of internal factors of enterprise competitiveness increases. In recent decades, the introduction of such technologies in service enterprises has become increasingly widespread, ranging from simple tools (e-mail or messengers) to global introduction in the business structure ( using electronic commerce or creating virtual enterprises). We are not even talking about the newest complex developments in the field of Internet technologies, but about the use of existing and simpler ones, which are increasingly used by enterprises. The basic directions of application of Internet technologies and advantages which a business entity in the service sector receives from it have been considered in the article.